Carbon nanofiber with selectively decorated pt both on inner and outer walls as an efficient electrocatalyst for fuel cell applications - Balan, Beena K.; Unni, SreeKuttan M.; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2009)
A novel electrocatalyst, with excellent Pi dispersion oil the inner and outer wall of a carbon nanofiber (CNF) was prepared by a modified polyol process in which both surface tension and polarity characteristics of the medium were properly adjusted to favor solution entry into the tubular region by capillary filling and homogeneous wetting of the inner wall surface by the solvents. The pristine CNF, which possesses an inherently active inner wall surface and inactive outer Wall surface, led to selective Pt deposition along the inner wall, whereas activation of the outer wall with chemical functionalization resulted in excellent dispersion of Pt along both inner and outer walls. Structural and morphological characterizations using high resolution transmission electron microscopy (HRTEM) and X-ray diffraction (XRD) revealed that when Pt could be dispersed along the inner as well as the Outer walls of CNF, the Pt particle size decreased to almost half as compared to the one With Pt decoration only along a single wall of the Substrate material. Further, electrochemical studies using cyclic voltammetry (CV) and rotating disk electrode (RDE) measurements revealed enhanced methanol oxidation and oxygen reduction properties, respectively. The electrochemical active area obtained for the catalyst with both inner and outer wall Pt decoration wits nearly two times higher than that corresponding to the one with only inner wall Pt decoration. Similarly, the rate constant for the oxygen reduction reaction displayed by this sample was four times higher in comparison with the sample prepared by Utilizing only one wall for Pt decoration.

Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrids for improved supercapacitor performance - Balan, Beena K.; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (RSC Advances, 2013)
Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrid electrode material which integrates dual wall decoration and interfacial area tuning for supercapacitor applications has been devised based on a simple approach. This is achieved by decorating RuO2 nanoparticles of size ca. 2-3 nm along the inner and outer walls of a hollow carbon nanofiber (CNF) support (F-20RuO(2)). In the next step, a proton conducting polymer, phosphoric acid doped polybenzimidazole (PBI-BuI), interface is created along the inner and outer surfaces of this material. A 103% increase in the specific capacitance is obtained for RuO2-PBI hybrid material as compared to that of F-20RuO(2) at the optimum level of the polymer wrapping. Apart from the high specific capacitance, the RuO2-PBI hybrid materials exhibit enhanced rate capability and excellent electrochemical stability of 98% retention in the capacitance. Such a remarkably high activity can be primarily attributed to the efficient dispersion of active sites achieved by properly utilizing inner and outer surfaces of CNF. Apart from this, the facile routes for ion transport created as a result of PBI incorporation coupled with excellent interfacial contact between the RuO2 and the electrolyte resulting in the improved utilization of the active material also contribute to the improved activity. In addition to this, the synergistic effects of pseudocapacitive contribution from both the PBI-BuI and RuO2 also contribute to the redefined performance characteristics.

Covalent organic framework-cadmium sulfide hybrid as a prototype photocatalyst for visible-light-driven hydrogen production - Thote, Jayshri; Aiyappa, Harshitha Barike; Deshpande, Aparna; Diaz, David Diaz; Kurungot, Sreekumar; Banerjee, Rahul (Chemistry A-European Journal, 2014)
CdS nanoparticles were deposited on a highly stable, two-dimensional (2D) covalent organic framework (COF) matrix and the hybrid was tested for photocatalytic hydrogen production. The efficiency of CdS-COF hybrid was investigated by varying the COF content. On the introduction of just 1 wt% of COF, a dramatic tenfold increase in the overall photocatalytic activity of the hybrid was observed. Among the various hybrids synthesized, that with 10 wt% COF, named CdS-COF (90: 10), was found to exhibit a steep H2 production amounting to 3678 mmolh(-1) g(-1), which is significantly higher than that of bulk CdS particles (124 mmolh(-1)g(-1)). The presence of a p-conjugated backbone, high surface area, and occurrence of abundant 2D hetero-interface highlight the usage of COF as an effective support for stabilizing the generated photoelectrons, thereby resulting in an efficient and high photocatalytic activity.
Keywords: charge transfer; covalent organic frameworks; hybrid materials; hydrogen production; Photocatalysis

Can enantiomer ligands produce structurally distinct homochiral MOFs? - Dubey, Mrigendra; Kumar, Ashish; Dhavale, Vishal M.; Kurungot, Sreekumar; Pandey, Daya Shankar (CrystEngComm, 2015)
Here, we report a self-assembled homochiral metal-organic framework [Cu-1.5(H2LL-leu)(Ac)H2O](n)center dot 3H(2)O (1) obtained from an L-leucine-derived ligand (H4L(L-leu)) and Cu(Ac)(2)center dot H2O in a 1 : 1 ratio. Coordination-induced conformational change in the ligand has been monitored by circular dichroism which has been further attested by synthesizing a D-leucine-containing enantiomer H4L D-leu and its Cu(II) complex [Cu-1.5(H2LD-leu)H2O](n)center dot 10H(2)O (2). Structure determination revealed entirely different structures for the homochiral MOFs (1 and 2) obtained from the L/D-leucine-derived enantiomer ligands under analogous reaction conditions. Further, structural dissimilarity in these MOFs has been judicially supported by proton conductance studies. MOF 1 shows higher proton (10(-5) S cm(-1)) conductance in comparison to 2 (10(-6) S cm(-1)) due to dissimilar alignment of the hydrogen-bonded water molecules in the hydrophilic pocket as well as crystal packing.

Carbon nanohorn-derived graphene nanotubes as a platinum-free fuel cell cathode - Unni, SreeKuttan M.; Illathvalappil, Rajith; Bhange, Siddheshwar N.; Puthenpediakkal, Hasna; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)
Current low-temperature fuel cell research mainly focuses on the development of efficient nonprecious electrocatalysts for the reduction of dioxygen molecule due to the reasons like exorbitant cost and scarcity of the current state-of-the-art Pt-based catalysts. As a potential alternative to such costly electrocatalysts, we report here the preparation of an efficient graphene nanotube based oxygen reduction electrocatalyst which has been derived from single walled nanohorns, comprising a thin layer of graphene nanotubes and encapsulated iron oxide nanopartides (FeGNT). FeGNT shows a surface area of 750 m(2)/g, which is the highest ever reported among the metal encapsulated nanotubes. Moreover, the graphene protected iron oxide nanoparticles assist the system to attain efficient distribution of Fe-N-x and quaternary nitrogen based active reaction centers, which provides better activity and stability toward the oxygen reduction reaction (ORR) in acidic as well as alkaline conditions. Single cell performance of a proton exchange membrane fuel cell by using FeGNT as the cathode catalyst delivered a maximum power density of 200 mW cm(-2) with Nafion as the proton exchange membrane at 60 degrees C. The facile synthesis strategy with iron oxide encapsulated graphitic carbon morphology opens up a new horizon of hope toward developing Pt-free fuel cells and metal-air batteries along with its applicability in other energy conversion and storage devices.
Keywords: carbon nanohorns; carbon nanotube; electrocatalyst; fuel cell; oxygen reduction reaction

Coherent fusion of water array and protonated amine in a metal-sulfate-based coordination polymer for proton conduction - Manna, Biplab; Anothumakkool, Bihag; Desai, Aamod V.; Samanta, Partha; Kurungot, Sreekumar; Ghosh, Sujit K. (Inorganic Chemistry, 2015)
A new function of metal-sulfate-based co-ordination polymer (CP) for proton,conduction Was investigated through rational integration of a continuous water array and protonated amine in the coordination space of the CP. The H-bonded arrays of watet molecules along with nitrogen-rich aromatic cation (protonated melamine) facilitate proton conduction in the compound under humid conditions. Although several reports of metal-oxalate/phosphate-based CPs showing proton conduction are known, this is the first designed synthesis of a metal sulfate-based CP bearing-Water arrays functioning as a solid-state proton conductor:

CoSe2 supported on nitrogen-doped carbon nanohorns as a methanol-tolerant cathode for air-breathing microlaminar flow fuel cells - Unni, SreeKuttan M.; Mora-Hernandez, Juan M.; Kurungot, Sreekumar; Alonso-Vante, Nicolas (Chemelectrochem, 2015)
The synthesis of CoSe2 nanoparticles supported on nitrogendoped carbon nanohorns (CoSe2/NCNH) and the influence of the interaction of the metal centre with the NCNH on the oxygen reduction reaction (ORR) are reported. CoSe2/NCNH shows a 50 mV lower onset overpotential and a 150 mV positive shift in the half-wave potential compared to CoSe2 supported on carbon and carbon nanohorns. This suggests that the intrinsic activity and the density of active reaction centres of CoSe2 are modified by NCNHs. An air-breathing direct meth-anol microlaminar flow fuel cell (mLFFC) is constructed using CoSe2/NCNH as a methanol-tolerant cathode catalyst. A maximum power density of 10.05 mWcm(-2) and a maximum current density of 124.20 mAcm(-2) are achieved with CoSe2/NCNH compared to the non-doped catalyst, CoSe2/C and Pt/C with 5m methanol as the fuel. The improved activity of CoSe2/ NCNH is attributed to the peculiar morphology and the nitrogen doping of the carbon nanohorns. This catalyst could be a suitable alternative to Pt.
Keywords: carbon nanohorns; chalcogenides; fuel cells; oxygen reduction reaction; platinum

Cu-Pt nanocage with 3-D electrocatalytic surface as an efficient oxygen reduction electrocatalyst for a primary Zn-air battery - Dhavale, Vishal M.; Kurungot, Sreekumar (ACS Catalysis, 2015)
Cu-Pt nanocage (CuPt-NC) intermetallic structures have been prepared by an in situ galvanic displacement reaction. The structures are found to be well organized within the framework demarcated with distinguishing arms, having clear edges and corners with a size of similar to 20 nm. The unique nanocage structure possessing large specific surface area and better structural integrity helps to achieve improved electrochemical oxygen reduction reaction activity and stability in alkaline solution in comparison to the commercially available 20 wt % Pt/C. CuPt-NC shows 50 mV positive onset potential shift with significantly higher limiting current in comparison to Pt/C. Interestingly, CuPt-NC has shown 2.9- and 2.5-fold improved mass activity and specific activity, respectively, for ORR at 0.9 V vs RHE in comparison to Pt/C. Moreover, the stability of CuPt-NC has been tested by an accelerated durability test under alkaline conditions. CuPt-NC has been subsequently utilized as the air electrode in a primary Zn-air battery and is found to possess 1.30- and 1.34-fold improved power density and current density at 1 V, respectively, in comparison to the state-of-the-art Pt/C catalyst. In addition, CuPt-NC has shown several hours of constant discharge stability at 20 mA cm(-2) with a specific capacity of 560 mAh gZn(-1) and energy density of 728 Wh kgZn(-1) in the primary Zn-air battery system.
Keywords: 3-D electrocatalytic surface; Cu-Pt nanocage; electrocatalyst; galvanic displacement; oxygen reduction reaction; solvothermal method; Zn-air battery

Cobalt-modified covalent organic framework as a robust wateroxidation electrocatalyst - Aiyappa, Harshitha Barike; Thote, Jayshri; Shinde, Digambar Balaji; Banerjee, Rahul; Kurungot, Sreekumar (Chemistry of Materials, 2016)
The development of stable, efficient oxygen evolution reaction (OER) catalyst capable of oxidizing water is one of the premier challenges in the conversion of solar energy to electrical energy, because of its poor kinetics. Herein, a bipyridine-containing covalent organic framework (TpBpy) is utilized as an OER catalyst by way of engineering active Co(II) ions into its porous framework. The as-obtained Co-TpBpy retains a highly accessible surface area (450 m(2)/g) with exceptional stability, even after 1000 cycles and 24 h of OER activity in phosphate buffer under neutral pH conditions with an overpotential of 400 mV at a current density of 1 mA/cm(2). The unusual catalytic stability of Co-TpBpy arises from the synergetic effect of the inherent porosity and presence of coordinating units in the COF skeleton.

Conjugated porous polymers as precursors for electrocatalysts and storage electrode materials - Bhosale, Manik E.; Illathvalappil, Rajith; Kurungot, Sreekumar; Krishnamoorthy, Kothandam (Chemical Communications, 2016)
Conjugated porous polymers were used as precursors to prepare nitrogen and sulphur doped carbon atoms, which were then used for oxygen reduction and energy storage.

Coordination polymers of Fe(III) and Al(III) ions with TCA ligand: distinctive fluorescence, CO2 uptake, redox-activity and oxygen evolution reaction - Dhara, Barun; Sappati, Subrahmanyam; Singh, Santosh K.; Kurungot, Sreekumar; Ghosh, Prasenjit; Ballav, Nirmalya (Dalton Transactions, 2016)
Fe and Al belong to different groups in the periodic table, one from the p-block and the other from the d-block. In spite of their different groups, they have the similarity of exhibiting a stable 3+ oxidation state. Here we have prepared Fe(III) and Al(III) based coordination polymers in the form of metal-organic gels with the 4,4', 4 `'-tricarboxyltriphenylamine (TCA) ligand, namely Fe-TCA and Al-TCA, and evaluated some important physicochemical properties. Specifically, the electrical conductivity, redox-activity, porosity, and electrocatalytic activity (oxygen evolution reaction) of the Fe-TCA system were noted to be remarkably higher than those of the Al-TCA system. As for the photophysical properties, almost complete quenching of the fluorescence originating from TCA was observed in case of the Fe-TCA system, whereas for the Al-TCA system a significant retention of fluorescence with red-shifted emission was observed. Quantum mechanical calculations based on density functional theory (DFT) were performed to unravel the origin of such discriminative behaviour of these coordination polymer systems.

Chitosan intercalated metal organic gel as a green precursor of fe entrenched and fe distributed N-doped mesoporous graphitic carbon for oxygen reduction reaction - Shijina, Kottarathil; Illathvalappil, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Yamaguchi, Takeo; Anilkumar, Gopinathan M.; Hareesh, U. S.; Sailaja, G. S. (Chemistryselect, 2017)
Herein, we present Metal-Organic Gel intercalated with chitosan, a `green'' precursor for the synthesis of intrinsic N-doped Fe entrenched (CHI-TMA-Fe-CW) and Fe distributed mesoporous graphitic carbon structures (CHI-TMA-Fe-CW-M1) with appreciable Oxygen Reduction Reaction (ORR) activity in alkaline medium. Modulation of the synthetic protocol as a function of reaction kinetics and gelation time while maintaining identical pyrolysis conditions (900 degrees C, flowing N-2 atmosphere) improves the microstructure, surface area and Fe distribution of the graphitic structures (CHI-TMA-Fe-CW-M1). CHI-TMA-Fe-CW has a Fe entrenched graphitic nanocapsule like morphology while Fe distributed mesoporous graphitic carbon sheets, with a specific surface area value of 565 m(2) g(-1) obtained by modulating the synthesis chemistry in CHI-TMA-Fe-CW-M1. The higher percentage of graphitic N in CHI-TMA-Fe-CW-M1 apparent from the XPS data validate that the modified synthetic method favours creation of more graphitic N sites contributing for better catalytic performance. CHI-TMA-Fe-CW-M1 catalyst exhibited comparable electrocatalytic activity with that of the commercially available Pt/C via an efficient four-electron-dominant ORR pathway with a positive onset potential value of 0.925 V vs RHE. Good durability of CHI-TMA-Fe-CW-M1 after 5000 cycles further confirm the prospects of MOG-chitosan and the feasibility to be used as a potential catalyst for ORR.
Keywords: electrocatalyst; fuel cell; Metal-Organic-Gel; oxygen reduction reaction

Convergent covalent organic framework thin sheets as flexible supercapacitor electrodes - Khayum, Abdul M.; Vijayakumar, Vidyanand; Karak, Suvendu; Kandambeth, Sharath; Bhadra, Mohitosh; Suresh, Karthika; Acharambath, Nikhil; Kurungot, Sreekumar; Banerjee, Rahul (ACS Applied Material & Interfaces, 2018)
Flexible supercapacitors in modern electronic equipment require light-weight electrodes, which have a high surface area, precisely integrated redox moieties, and mechanically strong flexible free-standing nature. However, the incorporation of the aforementioned properties into a single electrode remains a great task. Herein, we could overcome these challenges by a facile and scalable synthesis of the convergent covalent organic framework (COF) free-standing flexible thin sheets through solid-state molecular baking strategy. Here, redox-active anthraquinone (Dq) and pi-electron-rich anthracene (Da) are judiciously selected as two different linkers in a beta-ketoenamine-linked two-dimensional (2D) COF. As a result of precisely integrated anthraquinone moieties, COF thin sheet exhibits redox activity. Meanwhile, pi-electron-rich anthracene linker assists to improve the mechanical property of the free-standing thin sheet through the enhancement of noncovalent interaction between crystallites. This binder-free strategy offers the togetherness of crystallinity and flexibility in 2D COF thin sheets. Also, the synthesized porous crystalline convergent COF thin sheets are benefited with crack-free uniform surface and light-weight nature. Further, to demonstrate the practical utility of the material as an electrode in energy-storage systems, we fabricated a solid-state symmetrical flexible COF supercapacitor device using a GRAFOIL peeled carbon tape as the current collector.

Carbon derived from soft pyrolysis of a covalent organic framework as a support for small-sized RuO2 showing exceptionally low overpotential for oxygen evolution reaction - Chakraborty, Debanjan; Nandi, Shyamapada; Illathvalappil, Rajith; Mullangi, Dinesh; Maity, Rahul; Singh, Santosh K.; Haldar, Sattwick; Vinod, Chathakudath P.; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (ACS Omega, 2019)
Electrochemical water splitting is the most energy-efficient technique for producing hydrogen and oxygen, the two valuable gases. However, it is limited by the slow kinetics of the anodic oxygen evolution reaction (OER), which can be improved using catalysts. Covalent organic framework (COF)-derived porous carbon can serve as an excellent catalyst support. Here, we report high electrocatalytic activity of two composites, formed by supporting RuO2 on carbon derived from two COFs with closely related structures. These composites catalyze oxygen evolution from alkaline media with overpotentials as low as 210 and 217 mV at 10 mA/cm(2), respectively. The Tafel slopes of these catalysts (65 and 67 mV/dec) indicate fast kinetics compared to commercial RuO2. The observed activity is the highest among all RuO2-based heterogeneous OER catalysts-a touted benchmark OER catalyst. The high catalytic activity arises from the extremely small-sized (similar to 3-4 nm) RuO2 nanoparticles homogeneously dispersed in a micro-mesoporous (BET = 517 m(2)/g) COF-derived carbon. The porous graphenic carbon favors mass transfer, while its N-rich framework anchors the catalytic nanoparticles, making it highly stable and recyclable. Crucially, the soft pyrolysis of the COF enables the formation of porous carbon and simultaneous growth of small RuO2 particles without aggregation.

A copper(ii)-coordination polymer based on a sulfonic-carboxylic ligand exhibits high water-facilitated proton conductivity - Tayade, Sakharam B.; Illathvalappil, Rajith; Lapalikar, Vaidehi; Markad, Datta; Kurungot, Sreekumar; Pujari, Bhatchandra; Kumbhar, Avinash S. (Dalton Transactions, 2019)
Proton conduction ability has been investigated in a new Cu(ii) based coordination polymer (CP), {[Cu-2(sba)(2)(bpg)(2)(H2O)(3)]center dot 5H(2)O}(n) (1), synthesized using the combination of 4-sulfobenzoic acid (4-Hsba) and bipyridine-glycoluril (BPG) ligands. Single crystal X-ray structure determination revealed that 1 features 1D porous channels encapsulating a continuous array of water molecules. Proton conductivity measurements reveal a high conductivity value of 0.94 x 10(-2) S cm(-1) at 80 degrees C and 95% RH. The activation energy (E-a) of 0.64 eV demonstrates that the solvate water, coordinated water and hydrophilic groups in the channels promote the mobility of protons in the framework. Water sorption measurements exhibited hysterical behaviour with a high uptake value of 379.07 cm(3) g(-1). Time-dependent measurements revealed that the proton conductivity is retained even after 12 h of measurements. The proton conduction mechanism was validated by ab initio electronic structure calculations using the Nudged Elastic Band (NEB) method with molecular dynamics (MD) simulation studies. The theoretical activation energy is calculated to be 0.54 eV which is in accordance with the experimental value.

Cubic palladium nanorattles with solid octahedron gold core for catalysis and alkaline membrane fuel cell applications - Singh, Prem; Sonika; Gangadharan, Pranav K.; Khan, Ziyauddin; Kurungot, Sreekumar; Jaiswal, Amit (ChemCatChem, 2019)
Herein, we report the synthesis of palladium nanorattles (Au-Pd NRTs) comprising of a gold octahedral core caged within a thin porous cubic palladium shell. The introduction of core-shell and porous architecture was realized by combining seed mediated and galvanic replacement reaction techniques. Next, we examined the catalytic efficiency of the nanocatalyst in comparison with solid palladium nanocube (Pd-NC) of similar size for the degradation of p-nitrophenol and organic dyes. The rate constant of Au-Pd NRTs was found nearly 12 times higher than the Pd-NCs. Further, we exploited our catalyst for electrochemical oxygen reduction reaction (ORR) and observed its high intrinsic ORR activity. Compared with commercialized Pt/C, the Au-Pd NRT displayed nearly comparable onset and half-wave potential values and excellent durability upon potential cycling. The system level validation in a single-cell mode of alkaline exchange membrane fuel cell also confirms the efficiency of the present catalyst to serve as a potential cathode catalyst for realistic device applications.
Keywords: alkaline exchange membrane fuel cell; electrocatalysis; nanorattles; ORR; Pd nanoparticle

Co (9) S (8) nanoparticle-supported nitrogen-doped carbon as a robust catalyst for oxygen reduction reaction in both acidic and alkaline conditions - Illathvalappil, Rajith; Kurungot, Sreekumar (ChemElectroChem, 2020)
The present work illustrates the synthesis of an efficient and durable catalyst for electrochemical oxygen reduction reaction (ORR) which is active both in the alkaline and acidic conditions by dispersing few-layer graphitic carbon coated Co(9)S(8)nanoparticles on the nitrogen-doped carbon (NVC-G) support (Co9S8/NVC-G). The size of the Co(9)S(8)nanoparticles is nearly 7-8 nm and the particles are found to be dispersed homogeneously on the NVC-G support. The few-layer graphitic carbon formed on the surface of Co(9)S(8)nanoparticles is assisting to accomplish their small size and it also prevents agglomeration of the nanoparticles. The ORR activity of the obtained material was analyzed in both 0.1 M KOH and 0.5 M H(2)SO(4)solutions. Co9S8/NVC-G displays nearly 70 mV overpotential compared to thestate-of-the-artPt/C in 0.1 M KOH solution. The half-wave potential (E-1/2) difference of the present system is nearly 75 mV with the commercial Pt/C. Co9S8/NVC-G displays promising ORR activity in the acidic conditions as well with nearly 140 mV overpotential compared to its Pt/C counterpart. The system shows about 170 mV lowerE(1/2)value with Pt/C. The system shows good stability both in acidic and basic conditions compared to the Pt/C system. Finally, testing of a single cell of a polymer electrolyte membrane fuel cell (PEMFC) was performed by employing Co9S8/NVC-G as the cathode catalyst and Nafion-212 as the proton exchange membrane. The system displays a maximum power density of 245 mW cm(-2)in H-2-O(2)and 115 mW cm(-2)in H-2-air feeding conditions.
Keywords: cobalt sulfide; fuel cells; Nanoparticles; nitrogen-doped carbon; oxygen reduction reaction

Co@CoAl-layered double hydroxide/nitrogen-doped graphene composite catalyst for Al-H2O-based batteries: simultaneous hydrogen production and electricity generation - Nadeema, Ayasha; Pandurang Kharabe, Geeta; Prakash Biswal, Dibya; Kurungot, Sreekumar (ChemElectroChem, 2020)
Currently, the low energy efficiency of water electrolysis has compelled research toward the development of novel and energy-effective strategies for low-cost H-2 generation. In this context, we report a new concept of simultaneous H-2 and electricity generation by separating out the exothermic self-sustained Al-H2O reaction via electrochemistry. In addition, to catalyze the cathodic water reduction reaction, a single-pot and environmentally benign synthesis method is adopted. It results in the design of an electrocatalyst composed of Co@CoAl-layered double hydroxide core-shell nanospheres anchored over in situ generated N-doped graphene. Toward the water reduction reaction, the designed catalyst shows a negative voltage shift of mere around 113 mV with respect to the commercial Pt/C catalyst to reach the benchmark 10 mA cm(-2), with excellent stability of approximately 86 % voltage retention after 12 h of continuous operation. The catalytic superiority of our material is evident when taken for battery-level testing; the fabricated device was able to deliver an average output voltage of around 0.95 V at a discharge current density of 5 mA cm(-2) along with H-2 liberation, which was also detected and quantified through gas chromatography.
Keywords: Al-H2O fuel cells; chronopotentiometry; core-shell structures; hydrogen evolution reaction; layered double hydroxides

Co-Ni layered double hydroxide for the electrocatalytic oxidation of organic molecules: an approach to lowering the overall cell voltage for the water splitting process - Shilpa, Nagaraju; Pandikassala, Ajmal; Krishnaraj, Perayil; Walko, Priyanka S.; Devi, R. Nandini; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2022)
Electrocatalytic oxidation of simple organic molecules oilers a promising strategy to combat the sluggish kinetics of the water oxidation reaction (WOR). The low potential requirement, inhibition of the crossover of gases, and formation of value-added products at the anode are benefits of the electrocatalytic oxidation of organic molecules. Herein, we developed cobalt-nickel-based layered double hydroxide (LDH) as a robust material for the electrocatalytic oxidation of alcohols and urea at the anode, replacing the WOR. A facile synthesis protocol to form LDHs with different ratios of Co and Ni is adapted. It demonstrates that the reactants could be efficiently oxidized to concomitant chemical products at the anode. The half-cell study shows an onset potential of 1.30 V for benzyl alcohol oxidation reaction (BAOR), 1.36 V for glycerol oxidation reaction (GOR), 1.33 V for ethanol oxidation reaction (EOR), and 1.32 V for urea oxidation reaction (UOR) compared with 1.53 V for WOR. Notably, the hybrid electrolyzer in a full-cell configuration significantly reduces the overall cell voltage at a 20 mA cm(-2) current density by similar to 15% while coupling with the BAOR, EOR, and GOR and similar to 12% with the UOR as the anodic half-cell reaction. Furthermore, the efficiency of hydrogen generation remains unhampered with the types of oxidation reactions (alcohols and urea) occurring at the anode. This work demonstrates the prospects of lowering the overall cell voltage in the case of a water electrolyzer by integrating the hydrogen evolution reaction with suitable organic molecule oxidation.
Keywords: electrocatalytic oxidation; energy conversion; imidazole mediated; Layered compounds; water splitting

Chemically gradient hydrogen-bonded organic framework crystal film - Mohammed, Abdul Khayum; Raya, Jesus; Pandikassala, Ajmal; Addicoat, Matthew A.; Gaber, Safa; Aslam, Mohamed; Ali, Liaqat; Kurungot, Sreekumar; Shetty, Dinesh (Angewandte Chemie-International Edition, 2023)
Hydrogen-bonded organic frameworks (HOFs) are ordered supramolecular solid structures, however, nothing much explored as centimetre-scale self-standing films. The fabrication of such crystals comprising self-supported films is challenging due to the limited flexibility and interaction of the crystals, and therefore studies on two-dimensional macrostructures of HOFs are limited to external supports. Herein, we introduce a novel chemical gradient strategy to fabricate a crystal-deposited HOF film on an in situ-formed covalent organic polymer film (Tam-Bdca-CGHOF). The fabricated film showed versatility in chemical bonding along its thickness from covalent to hydrogen-bonded network. The kinetic-controlled Tam-Bdca-CGHOF showed enhanced proton conductivity (8.3x10(-5) S cm(-1)) compared to its rapid kinetic analogue, Tam-Bdca-COP (2.1x10(-5) S cm(-1)), which signifies the advantage of bonding-engineering in the same system.
Keywords: Chemical Gradience; Crystal Films; Free-Standing Films; hydrogen-bonded organic framework; Interfacial Chemistry; proton conductivity

Cobalt-manganese modified theophrastite phase of nickel hydroxide nanoflower arrays on nickel foam as a self-standing bifunctional electrode for overall water electrolysis - Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Barik, Sidharth; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Kurungot, Sreekumar (Sustainable Energy & Fuels, 2023)
Designing and developing self-supported electrodes for water electrolysis is attractive as compared to conventional catalyst-coated electrodes. Herein, a (Co0.3Mn0.1Ni0.6)(OH)(2)/NF nanocomposite is prepared by anchoring (Co0.3Mn0.1Ni0.6)(OH)(2)via simple one-pot hydrothermal synthesis on nickel foam. The presence of Mn induces the external electronic structure of Co(OH)(2), and this also improves the electrochemically active surface area (ECSA). These favor better accessibility of active sites and increased intrinsic activity for the OER and HER. (Co0.3Mn0.1Ni0.6)(OH)(2)/NF has shown promising electrochemical activity toward the OER and HER in a 1 M KOH electrolyte, with an overpotential of 270 mV for the OER and 163 mV for the HER to deliver 10 mA cm(-2) current density. The overall water splitting was performed by employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as both the cathode and anode by displaying a voltage of 1.62 V at 10 mA cm(-2), which is comparable to that extracted from a similar system based on the state-of-the-art Pt/C@NF cathode and RuO2@NF anode (1.60 V at 10 mA cm(-2)) standard electrode pair. Interestingly, at high current densities, the (Co0.3Mn0.1Ni0.6)(OH)(2)/NF//(Co0.3Mn0.1Ni0.6)(OH)(2)/NF system displayed better overall water splitting performance (1.78 V at 100 mA cm(-2)) compared to its Pt/C@NF//RuO2@NF (1.89 V at 100 mA cm(-2)) counterpart while displaying a stable output during the evolution period that lasted for 24 h. The amounts of H-2 and O-2 produced are estimated to be 701.2 and 358.6 mmol, respectively, at a time interval of 1 h; these amounts correspond to an similar to 1 : 2 ratio of O-2 and H-2, respectively. This study confirms the capability for employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as a bi-functional and self-standing electrode for the realistic demonstrations of overall water splitting applications.

Cathode|electrolyte interface engineering by a hydrogel polymer electrolyte for a 3D porous high-voltage cathode material in a quasi-solid-state zinc metal battery by in situ polymerization - Puthiyaveetil, Priyanka Pandinhare; Torris, Arun; Dilwale, Swati; Kanheerampockil, Fayis; Kurungot, Sreekumar (SMALL, 2024)
This work highlights the development of a superior cathode|electrolyte interface for the quasi solid-state rechargeable zinc metal battery (QSS-RZMB) by a novel hydrogel polymer electrolyte using an ultraviolet (UV) light-assisted in situ polymerization strategy. By integrating the cathode with a thin layer of the hydrogel polymer electrolyte, this technique produces an integrated interface that ensures quick Zn2+ ion conduction. The coexistence of nanowires for direct electron routes and the enhanced electrolyte ion infiltration and diffusion by the 3D porous flower structure with a wide open surface of the Zn-MnO electrode complements the interface formation during the in situ polymerization process. The QSS-RZMB configured with an integrated cathode (i-Zn-MnO) and the hydrogel polymer electrolyte (PHPZ-30) as the separator yields a comparable specific energy density of 214.14 Wh kg(-1) with that of its liquid counterpart (240.38 Wh kg(-1), 0.5 M Zn(CF3SO3)(2) aqueous electrolyte). Other noteworthy features of the presented QSS-RZMB system include its superior cycle life of over 1000 charge-discharge cycles and 85% capacity retention with 99% coulombic efficiency at the current density of 1.0 A g(-1), compared to only 60% capacity retention over 500 charge-discharge cycles displayed by the liquid-state system under the same operating conditions.
Keywords: cathode-electrolyte interface tuning; dendrite inhibition; epitaxial zinc deposition; hydrogel polymer electrolyte; In situ polymerization; Quasi solidstate rechargeable zinc metal battery

Co-incorporated N-doped micro-meso porous carbon as an electrocatalyst for oxygen reduction reaction and Zn-air battery - Priya, Vaishna K.; Kharabe, Geeta Pandurang; Barik, Sidharth; Mohamed, A. Peer; Kurungot, Sreekumar; Hareesh, Unnikrishnan Nair Saraswathy (Energy and Fuels, 2024)
Metal-organic frameworks are considered ideal precursors for the preparation of transition-metal, heteroatom-doped carbon catalysts that are perceived to be efficient electrocatalysts for energy storage devices. Herein, we demonstrate the synthesis of ZIF-67-derived Co-incorporated N-doped porous carbon catalysts supported on high surface area microporous carbon prepared from a lotus seed shell. The combination of the two carbon catalysts in different weight ratios resulted in Co-incorporated N-doped carbon sheets with tuned surface area and porosity, enabling enhanced oxygen reduction reaction (ORR) activity in an alkaline medium. The optimized carbon catalyst ZL 600 (3:1) exhibited a half-wave potential of 0.79 V vs RHE and a limiting current density of -4.38 mA cm(-2) in 0.1 M KOH solution with higher stability and methanol tolerance. The optimized sample ZL 600 (3:1) demonstrated as a cathode in a zinc-air battery exhibited an open circuit voltage of 1.29 V with a flat discharge profile at a current rate of 10 mA cm(-2). The homemade system produced a specific capacity of 610 mAh g(-1) and a peak power density of 111 mW cm(-2), comparable to the cathode made with Pt/C. The high micro-mesoporosity, pyridinic and pyrrolic nitrogen contents, as well as enriched Co-active centers protected by carbon sheets favorably contributed to the efficient ORR mechanism.

Conductive metal-organic frameworks for zinc-air battery application: design principles, recent trends and prospects - Devi, Bandhana; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2024)
Electrochemical energy conversion and storage systems have an indispensable place in the modern world to fulfill the increasing energy demands. Among the different storage devices, rechargeable zinc-air batteries (ZABs) have become one of the most promising energy technologies owing to the abundance and inexpensiveness of Zn, simple operation, environmental friendliness, and reasonable energy density. However, the sluggishness of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) occurring in ZABs is a serious obstacle in their progress and commercialization. This creates a need for the development of efficient bifunctional electrocatalysts for ORR and OER. Conductive metal-organic frameworks (cMOFs) imbibing the general properties of MOFs, like high surface area, tunable porosity, redox-active centers, and additional intrinsic conductivity, can be a very lucrative option for developing bifunctional ORR and OER electrocatalysts for ZAB applications. In this review, we discuss the conductivity and design strategies of conductive MOFs, the basic configuration of ZABs, and the use of cMOFs for ZAB applications. The future directions for the improvement of cMOFs for ZABs have been provided, which hopefully will incite interest among researchers for further exploring cMOFs for ZABs. Electrochemical energy conversion and storage systems have an indispensable place in the modern world to fulfill the increasing energy demands.
Keywords: Biofunctional Oxygen Electrocatalyst; Electrical conductivity; Energy storage; Fuel-Cells; li-ion batteries